Development of evaluative criteria for student teaching programs in the seven public regional normal schools in the Philippines with particular application to the Leyte Normal School - Ramo, Magdalena S. 1923- (Quezon City, Philippines College of Education, University of the Philippines Diliman, 1966)
This study determined the specific standards by which a program can be evaluated for its effectiveness in producing the desired quality of teachers. A set of evaluative criteria for student teaching programs was developed and then applied to the Leyte Normal School. The application demonstrates how to vitalize a tool in order to ascertain proper directions for improving student teaching programs. The Leyte Normal School Student Teaching Program was assessed in a spirit of self-criticism with a view to upgrade the quality of its student teaching.
Thesis (M.Ed.)--University of the Philippines
Keywords: Student teaching -- Philippines